Mangrove community-based management in Eastern Africa: experiences from rural Mozambique - Macamo, Célia da Conceição Felisberto; Inácio da Costa, Fátima; Bandeira, Salomao; Adams, Janine Barbara; Balidy, Henriques Jacinto (Frontiers in Marine Science, 2024)
Introduction This study investigated a community-based management model in a mangrove-dependent community in central Mozambique and its adequacy as a management tool for conservation. Methods Satellite images were used to map changes in mangrove cover between 1996 and 2017. Individual interviews and Focus Group Discussions were conducted with community members to understand the mangrove restoration processes and management models. Results and discussion After unsustainable exploitation that led to mangrove deforestation, the local community engaged in a restoration and management program that started in the late 1990s. Local norms were delineated by the Natural Resources Management Committee (NRMC) aiming at (1) reducing extractive uses by introducing alternative income generating activities; (2) awareness and mangrove planting and (3) law enforcement. Ten hectares of forest were rehabilitated. However, the management system fails to exclude illegal cutters and to enforce regulatory and sanctioning mechanisms, due to resource limitations. More involvement from government authorities and other stakeholders is needed to enhance law enforcement and explore opportunities for carbon trading, tourism and payment for ecosystem services. Additional recommendations are to develop a community management plan and create alternatives to mangrove products and income. Mangrove community-based management is increasingly advocated in many developing countries to promote sustainable utilization of resources and conservation. Understanding the reasons behind the limited success and lessons learnt at this site will guide similar programs elsewhere in Mozambique and other parts of the globe.